Assessment of locomotive syndromes in cancer patients: A comparative matching with non-cancer patients using propensity scores (肿瘤患者运动障碍综合征的评估: 一项使用倾向性评分与非肿瘤患者的匹配比较研究) - SHEN Yan (沈燕); SU Hui (苏慧); YANG Yuling (杨玉玲) (中西医结合护理, 2025)
Objective To evaluate the situation of locomotive syndrome in cancer patients and compare with non-cancer patients. Methods The test method for locomotive syndrome developed by the Japanese Orthopaedic Association was used to test cancer patients who had completed primary treatment and lived completely independently, and the data were compared with those of non-cancer subjects. Propensity score matching was used to match the background data. Data from 52 cancer patients (cancer group)and 76 non-cancer patients (non-cancer group) were compared. Results The cancer group had a significantly lower mean score of the two-step test than the non-cancer group (P=0. 002). The cancer group had a significantly lower standing test score than the non-cancer group (P＜0. 05). The average GLFS-25 score of the cancer group was significantly higher than that of the non-cancer group (P＜0. 001). A higher GLFS-25 score indicated that the subject had reduced motor function. The proportion of grade 2 locomotive syndrome in the cancer group was significantly higher than that in the non-cancer group (P＜0. 001). Conclusion Even cancer patients who have completed primary treatment and are fully self-care may have potentially impaired motor function. Timely screening and intervention of locomotive syndrome in cancer patients can help to maintain and improve the motor function of patients, and thus improve the prognosis. (目的 评估肿瘤患者运动障碍综合征的情况, 并与非肿瘤患者比较。方法 采用日本骨科协会制定的专业运动障碍综合征测试方法对已经完成主要治疗且生活完全自理的肿瘤患者进行测试, 并与非肿瘤受试者的数据进行比较。采用倾向评分匹配法对受试者背景资料进行匹配。比较52例肿瘤患者(肿瘤组)和76例非肿瘤患者(非肿瘤组)的数据。结果 肿瘤组的两步测试平均得分低于非肿瘤组(P=0. 002); 肿瘤组站立测试得分低于非肿瘤组(P＜0. 001); 肿瘤组的运动功能评估量表(GLFS-25)平均得分高于非肿瘤组(P＜0. 001)。较高的GLFS-25评分表明受试者运动功能降低。肿瘤组运动障碍综合征2级人数的比例高于非肿瘤组(P＜0. 001)。结论 即使是已经完成主要治疗并且完全自理的肿瘤患者, 其运动功能也可能存在潜在受损。对肿瘤患者进行及时的运动障碍综合征筛查并及时干预, 有助于维持和改善患者的运动功能, 进而改善预后。)